2004
DOI: 10.1039/b313777e
|View full text |Cite
|
Sign up to set email alerts
|

The lowest-lying excited singlet and triplet electronic states of propanal: an ab initio molecular orbital investigation of the potential energy surfaces

Abstract: This study explores the potential energy surfaces of the S 0 , S 1 and T 1 states using ab initio theory to provide insight into the spectroscopy, photochemistry and reaction dynamics of propanal. Minima associated with the formyl potential energy coordinate in the S 1 and T 1 states are found to be $60 out-of-phase with the S 0 state. Furthermore, the excited states possess a pyramidal formyl carbon atom that leads to a double minimum at AE33 and AE49 for the S 1 and T 1 states, respectively. An exploration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…There have been previous theoretical investigations of α-bond cleavage and other reaction pathways, particularly in linear saturated aldehydes, and α,β-unsaturated carbonyls. ,, There has been also been a number of studies of S 0 potential energy surfaces of carbonyls including Radom and co-workers’ thermochemical characterization of C 2 H 4 O stationary points . However, such studies use different levels of theory, making the results hard to compare quantitatively, as shown in Table S1 of the Supporting Information.…”
Section: Introductionmentioning
confidence: 99%
“…There have been previous theoretical investigations of α-bond cleavage and other reaction pathways, particularly in linear saturated aldehydes, and α,β-unsaturated carbonyls. ,, There has been also been a number of studies of S 0 potential energy surfaces of carbonyls including Radom and co-workers’ thermochemical characterization of C 2 H 4 O stationary points . However, such studies use different levels of theory, making the results hard to compare quantitatively, as shown in Table S1 of the Supporting Information.…”
Section: Introductionmentioning
confidence: 99%
“…Propionaldehyde (CH 3 CH 2 CHO), as a member of aliphatic aldehydes, shows similar chemical properties as its smaller counterparts, but its photochemistry is much less investigated. Kurosaki has demonstrated that CH 3 CHO and CH 3 CH 2 CHO in photolysis at 248 nm may show dynamic similarity for their molecular production, CH 3 CHO → CH 4 + CO and C 2 H 5 CHO → C 2 H 6 + CO. , Nevertheless, there is no experimental evidence to support such similarity in the energy flow between them. It is thus crucial to look into whether propionaldehyde is likely to exhibit a similar photodissociation feature.…”
mentioning
confidence: 99%
“…For the latter issue, it has been well established that there is a major isomerization pathway, involving the b-distonic ion ( CH 2 CH 2 CHOH 1 ) as an intermediate species and the enol ion (CH 3 CHQCHOH 1 ) as the most stable isomer for C 3 H 6 O 1 . 12,[18][19][20] If there is no additional photon absorption after ionization, previous experimental and computational results clearly show that the propanal cation essentially retains the structure of its neutral precursor for internal energies up to 0.66 eV. 13,20 Our estimated barrier height for the isomerization of CH 3 CH 2 CHO 1 to the b-distonic ion ( CH 2 CH 2 CHOH 1 ) through 1,4-H migration is also given to be about 0.61 eV, consistent with previous results.…”
Section: Resultsmentioning
confidence: 99%
“…10 In a subsequent work, they observed conformationally-specific photodissociation pathways for these two different conformers, producing 2propyl cation (2-C 3 H þ 7 ) from the gauche and cyclopropane cation (cyclic-C 3 H þ 7 ) from the anti, in the visible range of 480-700 nm which corresponds to excitation to the repulsive first excited electronic state of the ion. 11 As one of the simple aliphatic aldehydes, propanal and its cation have been the subject of a variety of experimental [12][13][14][15][16][17] and theoretical studies [18][19][20][21][22] both as a model polyatomic system and as one of the important intermediate species in the isomerization of organic ions with the CCCO frame in mass spectrometry. From a spectroscopic point of view, one interesting feature of propanal is that there are two distinct electronic origins through the lowest (n, 3s) Rydberg transitions, one for the cis conformer and another weaker origin displaced to B840 cm À1 higher energy for the gauche conformer, based on previous (2 þ 1) REMPI spectroscopic studies by Metha et al 23 and Pfab et al 24,25 The transition for cis-propanal is clearly dominated by a long progression of the in-plane deformation mode (v 15 ) due to large angle changes in the CCCO backbone, while the gauche-propanal transition shows only a weak v 15 progression.…”
Section: Introductionmentioning
confidence: 99%